On the Basis of Information-Discursive Analysis - Rasulov Zubaydullo Izomovich (Indonesian Journal of Innovation Studies, 2022)
In modern linguistics, the concept of "information" has become one of the leading conceptual units. We observe this even in the descriptions given to the linguistic phenomenon. As A.Y. Kibrik points out, “language is a multifunctional system with internal integrity and integrity. One of its main tasks is related to its actions in relation to information.”